2016
DOI: 10.1002/pbc.26183
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase‐associated pancreatitis is not predicted by hypertriglyceridemia or pancreatic enzyme levels in children with acute lymphoblastic leukemia

Abstract: AAP does not seem to be associated with HTG. Continuous monitoring of pancreas enzymes does not predict AAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…How elevated lipids in general, or following asparaginase and dexamethasone therapy, affect this mechanism is unknown. We have previously investigated whether patients with pancreatitis (n = 7) had higher levels of triglycerides than controls (n = 24) and found no association between triglycerides and pancreatitis . However, lack of power in this study could lead to type 1 error.…”
Section: Baseline Characteristics and Cumulative Incidences Of Pancrementioning
confidence: 81%
See 1 more Smart Citation
“…How elevated lipids in general, or following asparaginase and dexamethasone therapy, affect this mechanism is unknown. We have previously investigated whether patients with pancreatitis (n = 7) had higher levels of triglycerides than controls (n = 24) and found no association between triglycerides and pancreatitis . However, lack of power in this study could lead to type 1 error.…”
Section: Baseline Characteristics and Cumulative Incidences Of Pancrementioning
confidence: 81%
“…published in this journal that obesity in children with ALL was associated with risk of pancreatitis . Since obesity is an increasing global health issue, hypertriglyceridemia is a risk factor for pancreatitis in non‐ALL adults, and obesity and triglyceride levels are correlated, an association seems plausible, although a recent study failed to demonstrate hypertriglyceridemia as a risk for pancreatitis in children with ALL . Therefore, we aimed to reproduce this association and improve the understanding of risk factors for pancreatitis in childhood ALL.…”
Section: Baseline Characteristics and Cumulative Incidences Of Pancrementioning
confidence: 99%
“…In adults with non-malignant disorders, hypertriglyceridemia (above 10 times the UNL) has been associated with an increased risk of acute pancreatitis 185, 188, 190 , but so far this has not been replicated in children with ALL 191 . A few studies have indicated associations with development of ON and thrombosis 78, 83, 95, 158, 188, 192 , but no randomized studies have explored whether lipid-lowering interventions prevent these complications.…”
Section: Hyperlipidemiamentioning
confidence: 99%
“…The association between hypertriglyceridemia and other toxicities (thrombosis, osteonecrosis, and pancreatitis) has been previously studied. 6,[14][15][16][17] It has been suggested that hypertriglyceridemia may be associated with osteonecrosis and thrombosis, although the associations were not maintained in multivariate analyses. 6 However, there are few large-scale studies to support hypertriglyceridemia as an independent risk factor.…”
Section: Introductionmentioning
confidence: 99%